Impact of lifestyle behavior change on glycemic control in youth with type 2 diabetes. Issue 1 (4th April 2017) - Kriska, Andrea; El ghormli, Laure; Copeland, Kenneth C; Higgins, Janine; Ievers‐Landis, Carolyn E; Levitt Katz, Lorraine E; Trief, Paula M; Wauters, Aimee D; Yasuda, Patrice M; Delahanty, Linda M; ,
Abstract : Background: Little is known about the feasibility and impact of lifestyle intervention, determined by change in diet and cardiovascular fitness (CRF), on glycemic control in youth who are overweight with type 2 diabetes. This was examined in the Treatment Options for type 2 Diabetes in Adolescents and Youth (TODAY) clinical trial cohort from across 15 US centers. Subjects: TODAY enrolled 699 youth aged 10 to 17 years with type 2 diabetes <2 years and body mass index ≥85th percentile at baseline. Methods: Dietary data were collected by an interviewer‐administered food frequency questionnaire; CRF was assessed using a submaximal cycle ergometer test. Change from baseline in these variables was analyzed using generalized linear mixed models for both continuous and categorical measures. Models were adjusted for age, baseline HbA1c, treatment group, and medication adherence. Data were collected at baseline, 6, and 24 months. Trial registrationClinicalTrials.gov NCT00081328. Results: At 6 months, ~25% of females and ~33% of males improved CRF. In males, this was related to a decreased HbA1c ( P  = .001) and a lower percent experiencing glycemic failure (HbA1c ≥8%; P  = .007). Females who decreased their saturated fat intake and/or increased their fiber intake had lower HbA1c at month 24 ( P  = .01 and P  = .007, respectively). Males who increased their sweetened beverage intake at 6‐month follow‐up were at a 1.6‐fold higher risk of experiencing glycemic failure ( P  = .04). Conclusions: Few youth improved fitness and/or diet over time, although those who did showed a beneficial impact on glycemic outcomes. Although lifestyle behaviors are difficult to change in youth with type 2 diabetes, interventions are needed that are feasible (in scope, complexity, and demands), sustainable, and clinically meaningful.